2015
DOI: 10.1109/tpel.2014.2353055
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization and Topology Selection for a Module-Integrated Inverter

Abstract: As photovoltaic (PV) energy continues to gain market penetration, thanks in part to substantial cost reductions on the solar modules, attention is shifting to the balance-of-system performance and costs. This paper proposes an approach to explore the design limits of a module -integrated inverter by means of the component-level multi-objective optimization. A two-stage inverter along with an active filter to eliminate double-frequency content of the DC-link current is proposed for the topology of module-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…15, it has been shown that the THD of the output currents is always less than 5% as pre-calculated from Table 4. However, if the low order harmonics increased and lead the THD to exceed 5%, harmonic eliminators can be used in the control scheme to remove these components as shown in [1], but this will add to the complexity of the control system. For energy storage elements such as C p , C s in Cuk-module or L s and L p in other modules, the values are chosen to ensure that the element will withstand the peak value and to avoid saturation.…”
Section: ) Passive Elements and Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…15, it has been shown that the THD of the output currents is always less than 5% as pre-calculated from Table 4. However, if the low order harmonics increased and lead the THD to exceed 5%, harmonic eliminators can be used in the control scheme to remove these components as shown in [1], but this will add to the complexity of the control system. For energy storage elements such as C p , C s in Cuk-module or L s and L p in other modules, the values are chosen to ensure that the element will withstand the peak value and to avoid saturation.…”
Section: ) Passive Elements and Efficienciesmentioning
confidence: 99%
“…The remarkable development in the installed capacity of distributed generators (DGs) increases the international aspiration for improving the performance of power inverters employed in renewable energy systems (RESs) such as photovoltaic (PV) systems [1]. The employed inverters are required to have small size, light weight and low power losses.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, the DMPPT boost inductor size and mass are minimized and the energy captured by the PV module is maximized in [10]. Multi-objective optimization has been adopted in [19][20] to design the power stage of a Module-Integrated Inverter. In [21][22], NSGA-II algorithms are proposed as promising techniques to reach optima design specifications meeting design time requirement.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…To this end, the assessment of VSC topologies at different dc voltage levels has been a key research area that received interest recently [9], [16], [17]. This is also evidenced in the several demonstration projects that have been or being implemented around the globe.…”
Section: Introductionmentioning
confidence: 99%